Learning and Development (L&D) and Organisational Change in Nigeria National Petroleum Corporation Exploitation and Production Limited - Amadasun, Judith Oghogho; Erimife, Joy (NIU Journal of Social Sciences, 2026)
This study examined the relationship between learning and development and organisational change in NNPC Exploration & Production Limited, Benin City, Edo State. The study was motivated by the increasing need for organisations to adapt to technological advancement, competitive pressures, and changing operational demands through effective employee development initiatives. Specifically, the study sought to determine whether learning and development significantly relates with organisational change within the organisation. A survey research design was adopted for the study. The population comprised 1,116 staff members of NNPC Exploration & Production Limited, consisting of management, senior, and junior staff. Using the Taro Yamane formula, a sample size of 325 respondents was determined and questionnaires were administered across different departments and units of the organisation. Out of the questionnaires distributed, 292 valid copies were retrieved and used for analysis, representing an 89.8% response rate. Data collected were analysed using descriptive statistics such as frequency distribution, percentages, mean, and standard deviation, while regression analysis was employed to test the hypothesis with the aid of Statistical Package for Social Sciences (SPSS) version 24. The findings revealed that learning and development had a positive but statistically insignificant relationship with organisational change at the 5% level of significance [β = 0.105; t = 1.919; p > 0.05]. The study concluded that although learning and development contributes positively to organisational change, the existing programmes within the organisation may not be adequately aligned with organisational transformation objectives. The study therefore recommended that the organisation should redesign its learning and development programmes to focus more on change-oriented competencies, continuous employee development, technological adaptability, and regular evaluation of training effectiveness in order to enhance organisational change outcomes. Keywords: Learning and Development, Organisational Change, Human Resource Management, Employee Development, Oil and Gas Industry, NNPC Exploration and Production Limited.